1989
DOI: 10.1117/12.7977037
|View full text |Cite
|
Sign up to set email alerts
|

Moire Factors And Visibility In Scanned And Printed Halftone Images

Abstract: Unacceptable moire distortion may result when images that include periodic structures such as halftone dots are scanned. In the frequency domain, moire patterns correspond to visible aliased frequencies. In the spatial domain, moire patterns are evident as cyclic changes in the size of halftone dots, producing visible periodic "beat" patterns.Moire pattern formation depends on the following factors: (1) the halftone screen frequency, (2) the scan frequency, (3) the angle between the scan direction and the half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 1 publication
(1 reference statement)
0
7
0
Order By: Relevance
“…4,5 The common methods used to quantize a scanned halftone are error diffusion ͑ED͒, simple thresholding, rehalftoning, or descreening and rescreening. Quantization reduction via conventional ED typically produces fragmented dots ͓Fig.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The common methods used to quantize a scanned halftone are error diffusion ͑ED͒, simple thresholding, rehalftoning, or descreening and rescreening. Quantization reduction via conventional ED typically produces fragmented dots ͓Fig.…”
Section: Introductionmentioning
confidence: 99%
“…A. Steinbach and K. Y. Wong extended Huang's model to include the effects of scan aperture size and shape, and the reproduction printing process in the frequency domain [4]. J. Shu, R. Springer, and C. Yeh analyzed moire formation factors and derived a formula to manipulate these factors to minimize moire visibility [1]. J. Shu achieved moire elimination and tone correction using a local tonal compensation technique [5].…”
Section: Introductionmentioning
confidence: 99%
“…Much research has been done on the analysis and reduction of moire patterns by the various approaches as follows: (1) high frequency scanning (2) low pass filtering, (3) manipulation of the factors producing moire patterns, and (4) post-scan image processing algorithms [1][2][3][4]. A. Rosenfeld and A. Kak showed that moire patterns are caused by aliased frequencies produced when sampling images containing periodic structure [2].…”
Section: Introductionmentioning
confidence: 99%
“…To discover the solution of moiré noise reduction on various image applications, much research has been done by various approaches such as high frequency scanning, low pass filtering, manipulation of the factors producing moiré patterns, post-scan image processing algorithms [12][13][14][15], and etc. A. Rosenfeld and A. Kak showed that moiré patterns are caused by aliased frequencies when sampled images contain periodic structure [13].…”
Section: Introductionmentioning
confidence: 99%
“…Ville et al [19] proposed a nonlinear resampling method for moiré suppression. Shu et al [12] analyzed moiré formation factors and derived a formula to manipulate these factors to minimize moiré visibility. J. Shu achieved moiré elimination and tone correction using a local tonal compensation technique [20].…”
Section: Introductionmentioning
confidence: 99%